Maternal Vibrational Signals Reduce the Risk of Attracting Eavesdropping Predators - Hamel, Jennifer A.; Cocroft, Reginald B. (Frontiers in Ecology and Evolution, 2019)
Unintended receivers can be an important source of selection on social signals. Vibrational social signals are produced by diverse taxa, but most work on eavesdropping on social communication has focused on airborne signals. Few studies have examined whether predators and parasitoids exploit vibrational social signals, and whether vibrational communication systems have features to reduce apparency to unintended receivers. For a subsocial insect species (Hemiptera: Membracidae: Platycotis vittata), we first used a field playback experiment to show that offspring vibrational signals evoke maternal defense, and that maternal signals can inhibit offspring signaling. We next evaluated two potential benefits of inhibiting offspring signaling. We tested whether such inhibition increases the accuracy of offspring signals, as it does in a closely related species. We also tested whether by inhibiting offspring signals, mothers reduce the risk of attracting eavesdropping predators. Using playback experiments, we found that a vibrationally-sensitive predator attends to offspring but not maternal signals. In contrast, we found no evidence that inhibition increases the accuracy of offspring signals. Because predator eavesdropping is a likely cost of social communication for vibrationally signaling animals, we suggest that mechanisms to reduce apparency of such social signals may be common.